Peptides With Triplet-Tryptophan-Pivot Promoted Pathogenic Bacteria Membrane Defects - Chou, Shuli; Li, Qiuke; Nina, Zaitseva; Shang, Lu; Li, Jiawei; Li, Jinze; Wang, Zhihua; Shan, Anshan (Frontiers in Microbiology, 2020)
Development of probiotic-ineffective antimicrobial peptides (AMPs)-based coatings that can kill pathogenic bacteria at low concentrations but are essentially harmless (even high concentrations) to probiotic organisms is a relatively new trend for therapy against GI tract infections. In this study, a series of triplet-tryptophan-pivot peptides with various hydrophilic amino acids was constructed. One AMP in particular, S7, showed bactericidal activity against Staphylococcus epidermidis, Pseudomonas aeruginosa, Escherichia coli and antibiotic-resistant Staphylococcus aureus, yet was shown to be harmless to Lactobacillus rhamnosus, a key GI tract commensal. Furthermore, antibacterial mechanism assays, drug resistance assays, and mouse model tests suggested that S7 was useful in a clinical setting as it proved to significantly reduce bacterial load and cytokines (TNF-α, IL-6; P<0.05) with a low probability of resistance via bacterial membrane physical destruction and formation of intracellular ROS. Combined, the results show that a triplet-tryptophan-pivot peptide containing a pair of serine residues was an excellent pathogen-selective candidate for medical devices and was potentially useful in food preservation, crop protection and human health.